A QUANTITATIVE-ANALYSIS OF THE POLARIZATION REVERSAL IN THE 73 MOL PERCENT VINYLIDENE FLUORIDE-27 MOL PERCENT TRIFLUORETHYLENE COPOLYMER - Ferreira, GFL; Moreno, R. A. (American Institute of Physics (AIP), 1994)
We show that a time-dependent, effective-medium approximation essentially explains the time behavior of the polarization reversals obtained in doped copolymers of vinylidene fluoride and trifluorethylene at 60 degrees C by Ieda, Fukada, and Wada [J. Appl. Phys. 64, 2026 (1988)], who attributed the observed effects to charge accumulation at the boundaries of the permanently polarized crystallites. Moreover, the results seem to indicate that some hindrance (perhaps of mechanical origin) opposes the action of the switching electric field.